2003
DOI: 10.1128/aem.69.11.6628-6633.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Natural Viral Communities from Soil for Culture-Independent Analyses

Abstract: An essential first step in investigations of viruses in soil is the evaluation of viral recovery methods suitable for subsequent culture-independent analyses. In this study, four elution buffers (10% beef extract, 250 mM glycine buffer, 10 mM sodium pyrophosphate, and 1% potassium citrate) and three enumeration techniques (plaque assay, epifluorescence microscopy [EFM], and transmission electron microscopy [TEM]) were compared to determine the best method of extracting autochthonous bacteriophages from two Del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 47 publications
6
127
0
2
Order By: Relevance
“…SYBR Gold has so far been used to stain viruses in samples from the water column (McDaniel et al 2001, Yager et al 2001, Williamson et al 2002, Anesio et al 2004, Breitbart et al 2004, Brussard 2004, Lisle & Priscu 2004, Wen et al 2004) and sediment (Fischer et al 2003(Fischer et al , 2004 of aquatic systems, in soil samples (Williamson et al 2003) and human feces (Breitbart et al 2003). Direct comparison of staining viruses with SYBR Gold and the commonly used dye SYBR Green I has been made in 4 studies: (1) Chen et al (2001) reported that even when no antifading-solution was used, the fluorescence of SYBR Gold-stained viruses in marine water samples was stable for more than 2 min under EFM, while the SYBR Green I signal faded within 30 s. Using flow cytometry to enumerate Cyanophage P49, the mean fluorescence per P49 virus determined with SYBR Gold was about 2 times higher than that with SYBR Green I.…”
Section: Comparison Of Sybr Green I and Sybr Gold Viral Countsmentioning
confidence: 99%
“…SYBR Gold has so far been used to stain viruses in samples from the water column (McDaniel et al 2001, Yager et al 2001, Williamson et al 2002, Anesio et al 2004, Breitbart et al 2004, Brussard 2004, Lisle & Priscu 2004, Wen et al 2004) and sediment (Fischer et al 2003(Fischer et al , 2004 of aquatic systems, in soil samples (Williamson et al 2003) and human feces (Breitbart et al 2003). Direct comparison of staining viruses with SYBR Gold and the commonly used dye SYBR Green I has been made in 4 studies: (1) Chen et al (2001) reported that even when no antifading-solution was used, the fluorescence of SYBR Gold-stained viruses in marine water samples was stable for more than 2 min under EFM, while the SYBR Green I signal faded within 30 s. Using flow cytometry to enumerate Cyanophage P49, the mean fluorescence per P49 virus determined with SYBR Gold was about 2 times higher than that with SYBR Green I.…”
Section: Comparison Of Sybr Green I and Sybr Gold Viral Countsmentioning
confidence: 99%
“…While these model systems have provided valuable insights into phage-host interactions in soils, culture-independent detection and analyses will be critical in obtaining a more complete understanding of the ecological impacts of viruses in soils. As recently as 2003, the abundance of autochthonous viruses in soil was unknown (5,57). Previous assessments of viral abundance in soils were based on determination of PFU by using susceptible indicator strains (64), microscopic enumeration of optically active viruses such as baculoviruses (53), or PCR amplification of viral nucleic acids by using specific primers (43).…”
mentioning
confidence: 99%
“…The recovery rate was 37% of enterovirus according to Monpoeho et al (2001). Williamson et al (2003) proposed four elution buffers (10% beef extract, 250 mM glycine buffer, 10 mM sodium pyrophosphate, and 1% potassium citrate). Beef extract and glycine buffer were the most effective in eluting viable phages inoculated into soils, with up to 29% recovery.…”
Section: Virus Elution Methodsmentioning
confidence: 99%
“…TEM is the only method that provides data on both the abundance and morphology of virus-like particles (Borsheim et al 1990). However, the costs involved and technical aspects can lead to variable and inaccurate estimates of the total abundance (Sambrook et al 1989, Williamson et al 2003.…”
Section: Other Detection Techniquesmentioning
confidence: 99%